Faculty in Adult Degree Programs As Teachers of Adults and as Adult Learners - Jovita M. Ross-Gordon; Kayon Murray-Johnson (Adult Education Research Conference, 2015)
In this study we sought to discover how faculty working in the context of adult degree programs make sense of teaching adult learners. Research questions focused on how they perceived adult learners as well as how teaching in an adult-oriented degree program has influenced their teaching beliefs and practices.
Keywords: adult degree programs; adult undergraduates; faculty; teaching adults